PELATIHAN PENINGKATAN KECERAHAN WARNA IKAN CUPANG KELURAHAN SETONO KECAMATAN PEKALONGAN TIMUR KOTA PEKALONGAN - Tri Yusufi Mardiana; Linayati Linayati; Muhammad Bahrus Syakirin; Benny Diah Madusari; Awaliyah Feni Furoidah; Muhammad Zulkham Yahya; Nila Oktaviani (LPPM Universitas Pekalongan, 2022)
The purpose of the service community is to improve the knowledge and skills of cultivators so that the brightness of the color of betta fish is better and would bring them a higher income. The method of activity is training and counseling about how to increase the brightness of fish colors and masculinization of betta fish. The result of the service community describes that increasing knowledge was gained from 50 % to 70%. The brightness of the fish's color could be reached by adding artificial feed (pellets), natural feed, light, feed additives such as carrots, pumpkin, dragon fruit, and tomatoes. Increased knowledge of cultivators about the masculinization process was found from 20% to 90%. This value-based on the total of respondents who answered all correctly. The masculinization process could be done by using some natural ingredients as follow: honey, coconut water, sea cucumber as media for soaking the fish, and sea cucumber flour which is given to feed of fish. Keywords: betta fish, coconut water, masculinization, brightness